In-vitro Anti-cercarial activity of extracts and steroidal alkaloids from the stem bark of Holarrhena floribunda (G. Don) Dur. & Schinz - Isaac Kingsley Amponsah; Francis Ackah Armah; John Alake; Benjamin Kingsley Harley; Elikplim Kwesi Ampofo; Evelyn Asante-Kwatia; Aglomasa Bill Clinton; Benjamin Amoani; Isaac Tabiri Henneh (International Journal of Phytomedicine, 2020)
Context: Schistosomiasis continues to be the leading cause of morbidity and mortality among the neglected tropical diseases. Apart from the high cost of chemotherapy, concerns over drug resistance and tolerance have been raised in the past decade. Objective: The aim of the study was to evaluate the anticercarial activity of extracts and compounds from the stem bark of Holarrhena floribunda on cercaria of Schistosoma haematobium. Methods: Hydroethanolic and alkaloidal extracts from the stem bark of H. floribunda were tested on cercaria at concentrations between 500.00 and 15.625 μg/mL for 180 minutes and assessing the percentage viability at time intervals of 0, 15, 30, 60, 120 and 180 minutes. Praziquantel, used as reference drug, and the isolated compounds were tested at similar concentrations. The cercaria mortalities and IC50 of extracts and compounds were estimated after 30 minutes of incubation. Results: The 70 %v/v ethanol extract showed the highest activity (IC50=20.09±1.11 μg/mL) with praziquantel giving IC50 of 695.50±1.12. The alkaloids holonamine, holadienine and conessine, isolated from the stem bark, showed considerable cercaricidal activity with the latter recording an IC50 of 33.28±1.04. Conclusion: The study gives first-hand knowledge of the anti-cercarial activity of H. floribunda and its steroidal alkaloids. This gives credence to the traditional uses of the plant as an anti-parasitic agent.